Beyond a Capitalist Atlantic: Fish, Fuel, and the Collapse of Cheap Nature in Ireland, Newfoundland, and Nigeria. Issue 1 (May 2019) - Paye, Michael
Abstract : Irish director Risteard O'Domhnaill's 2010 film, The Pipe, documents the battle of a small Mayo community against the Corrib gas pipeline project, following a number of local residents in their eight-year struggle against state-sponsored and corporate violence. In his next major production, Atlantic (2016), a comparative documentary of fishing and fossil-fuel industries in Ireland, Newfoundland, and Norway, O'Domhnaill retreats from the possible anti-systematicity of the Rossport struggle, taking a reformist, nationalist attitude to the question of oil and fish extraction. In this article, I will demonstrate how O'Domhnaill naturalizes this mobilization and 'cheapening' through a vocabulary of rightful ownership and human-centric dominance. Using world-ecological and energy humanities theories, I will then demonstrate that numerous other contemporary depictions of life and labour at the fish and oil frontiers, across the Global North and South, articulate how systemic contradiction materializes as environmental violence, focusing on works by Irish author Mike McCormack, Canadian author Lisa Moore, and Nigerian author Nnedi Okorafor.